ASSESSMENT OF CHALLENGES AND PROSPECTS OF LOCAL MILK SUPPLY ON MARKET PERFORMANCE: A CASE OF ETHIOPIA, HORN OF AFRICA - Gada Gizachew Wakjira; Shashi Kant (JURNAL PETERNAKAN SABANA, 2022)
The study aims at exploring the challenges and prospects of local milk supply in West Guji Zone. The study was conducted in three local administration of West Guji Zone; namely Bule Hora, Dugda Dawa, and Surro Bargudda. Milk was the most important dairy product marketed in the areas, so, the study was focused only on milk. Dairy Farmers from each local administration were selected using Proportional Probability to Size (SPSS version 22). The research was designed with cross sectional survey design for the small holder dairy farmers and census design for the Local Milk suppliers. Data were collected from 118 small holder House hold dairy farmers and 71 Local Milk suppliers and Small Holders Farmers 24 Totally 213 respondents Distributed questionnaire. Survey data collected from three local administrations was analyzed by using descriptive analysis.